Crop production amid climate change and river water level fluctuation at northeastern region of Bangladesh: A time series analysis (International Journal of Agricultural Research, Innovation and Technology, 2023)
The overall goal of this study was to examine the effects of climate change on the yield of four distinct crops (Aus, Aman, Boro and Wheat) in Sylhet by using secondary climate data from 1970 to 2020. The study's other goal is to assess the impact of river water levels on crop productivity in Sylhet over time. Data on crop productivity, weather variability and river water levels were gathered from the various fields. Yield vs. climatic correlation was discovered in the study, and this correlation varied according to season. To estimate the impact of climate change on rice yield, a multiple regression model is used. Climate variables in the model were found to account for 11% of the overall variation in Aus rice yield. The relationship between relative humidity and maximum temperature is positive and statistically significant. Other variables had no effect on yield because they were not significant. Furthermore, Regression results indicated that climate variables account for 60.6 percent of the overall variation in Aman rice output. Relative humidity, on the other hand, can undermine the yield. Climate variables account for 53.5 percent of the overall variation in Boro rice output, according to the findings. As a result, an increase in rainfall may have a negative impact on Boro rice yield. Maximum and minimum temperatures might have a favorable impact on Boro rice yield. Increases in maximum temperature, on the other hand, can considerably boost Wheat yield while decreases in minimum temperature can diminish Wheat yield. On the other side, the results of the regression analysis suggest that river water level has a minor impact on Aus, Aman, and Boro yield. However, as the model demonstrates, the river water level can have an impact on wheat yield. The impact of temperature and rainfall on water level was also investigated in this study because the regression model failed to produce positive results. Surprisingly, the model performs well, despite the fact that maximum temperatures have a negative impact on water levels in the Aus and Aman seasons. This shows that if warmer temperatures aid raises Aus and Aman yields, then the water level cannot sabotage the yield rise. Rainfall has a favorable impact on the water levels in the Aus, Aman, and Boro seasons, but has a negative impact on the water levels in the Wheat season.Int. J. Agril. Res. Innov. Tech. 12(2): 18-26, December 2022